Focus génétique sur Les Armes miraculeuses d’Aimé Césaire - Alex Gil (Continents manuscrits)
What if we insisted on reading the genesis of texts in non-teleological ways? Would it still be genetic criticism? We often fail to see—or remember—that the Text in question is only a function of a series of textual events, original publication being only but one of them. In the case of the early Aimé Césaire, that textual field can be characterized as a nebulous playground, rife with possibilities. Césaire worked on several editorial and literary projects during the period 1941‑1946, many of them invisible or unrecognizable unless we bracket bibliographic teleology, and many of them characterized by an ongoing effort to re-contextualize pre-existing texts. Out of this explosion of textual vagrancy we can glimpse a work that never was, and yet, was in many ways: A long poem, Le Grand Midi, obfuscated by a smaller poem published in Les Armes miraculeuses, « Le Grand Midi. » In this study we trace the history of this phantom poem, and in passing, without privileging it, we outline the contours of the textual field out of which was born Césaire’s first published book of poetry.